Dim blue light colour reduces the activities and improves the performance of Indian River broilers under Egyptian conditions - MOUSA-BALABEL, TM; AL-MIDANY, SA; ALGAZZAR, WZ (Journal of the Hellenic Veterinary Medical Society, 2021)
Poultry producers accustomed to use light colours in broiler production as atrial to increase their productivity, especially in the developing countries to cover the animal protein gap. This experiment was planned to study the effect of different blue light colour intensities (high, medium and dim) on a recently imported Indian River (IR) broilers to Egypt. In this study, 270 one-day old Indian River broiler chicks were used. The birds were exposed to high blue light intensity (HBLI), medium blue light intensity (MBLI) and dim blue light intensity (DBLI), through a monochromatic lighting system that was installed in different rooms for 24 hours daily. The birds were randomly divided and housed into three well controlled pens of 5.46 m2 with three replicates of 30 each using a density of 17 birds/m2 in the room. The results showed that the broilers reared under DBLI had a significantly (p< 0.05) higher body weight, body weight gain, Newcastle disease virus antibody titer and foot pad dermatitis with obviously, economic Feed conversion ratio (FCR) and low activities and heterophyil/lymphocyte ratio in comparing with (MBLI) and (HBLI). In conclusion, poultry producer can use dim blue light in their farms to reduce the activities and increase the productivity of the birds.